Students’ Expectations of Offline Learning Road to Endemic Covid-19 Status as the Effect of Online Learning - Rindu Alriavindrafunny (Jurnal Gantang, 2022)
Many methods and strategies of learning were being searched, made, and invented by a lecturer to provide an effective online learning process. Two years passed, and now Indonesia is on the road to endemic of covid-19 status, which soon caused the permission for offline learning. Indeed, students have their own expectations for this condition. Do they like it? Do they have difficulties so far? Do they want other methods? or other expectations of students which have not been explored yet? Therefore, this research will explore students' expectations of welcoming offline learning using a qualitative research method. The questionnaire was used as the instrument to collect the data from the students in the first year of the pandemic. The instrument mostly asked about the students' opinion of their online learning, then related to their expectations when it became offline learning soon. It was simply analyzed using excel to show the percentage of each data. The result showed that 75% did not like online learning since it impacts their score, which decreased from an average of about 70 to 50. Therefore, many students expect to understand the material with offline learning (80%) better than online. The reason for being less understandable with online learning and the decreasing score of students, becomes the evaluation of online learning found in this research. That strongly becomes the reason why the students expect to have a better understanding of offline learning in 2022